Cost Analysis of Hybrid Restructuration for Distribution System to Improve Voltage and Minimize Losses - Firas M.F Flaih; Lin Xiangning; Samir M. Dawoud; Mohammed R. Almallah (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Current situation in Iraq had led to extensive blackouts which needs an expansion in generation capacity. On the other hand the government has reduced the budget allocated for energy resource development and it seems this situation will sustain for the coming years.  So the fulfilment of the load demand is the biggest challenge for the ministry of electricity with limited budget. In this paper the authors have proposed a method to reduce the power losses and therefore improve the voltage profile for low voltage (LV) distribution system that results in reduction of blackouts. The method involves the repositioning of the distribution transformer (DTR) from the existing location and the replacement of the overhead conductor cross section area for an existing low voltage distribution system (LVDS). This method has been applied to a 20-node low voltage radial distribution network in the general directorate of north distribution electricity (GDNDE), Iraq, where voltage profile and losses are unsatisfactory. Results demonstrate the effectiveness of the proposed method also in terms of the economic feasibility. It is observed that the system average voltage profile is improved by 15%, tail end voltage enhanced by 19.7% and losses are reduced by 78% for existing the LVDS.